How justified is abandoning money from monetary policy? Evidence from dynamically simulated ARDL - Masudul Hasan Adil; Neeraj R. Hatekar (Cogent Economics & Finance, 2023)
AbstractThe stable money demand function is a crucial policy tool of the monetary policy of any central bank, which links the monetary sector of an economy to its real sector. Notably, after the global financial crisis of 2007–08, the role of money has come to be envisaged as an essential issue while formulating and conducting the monetary policy, especially at zero lower bound. It is crucial to know whether money demand is stable for inferring a sound monetary policy. To this end, the present study examines the short- and long-run money demand relationship and its stability in India from 2006:Q3 to 2019:Q4. The study has employed a dynamically simulated autoregressive distributed lag (ARDL) cointegration approach, which shows a well-specified and stable money demand in India after incorporating the inflation forecast variable as one of the essential determinants along with other covariates. Furthermore, the dynamically simulated impulse response also supports the economic relationship among variables. The current finding of stable money demand implies a policy implication in terms of focusing on monetary aggregate, in the ongoing flexible inflation targeting framework, as one of the essential information or indicator variables, which acts as a long-term assessment of short-term interest rate setting behaviour to achieve the macroeconomic goals.